Potency Study of N-Hexane Extracts of Black Plum (Syzygium cumini (L.) Skeels) Intheinhibitation of Growth Salmonella typhi and Candida sp. - Saida Rasnovi; Risa Nursanty (Jurnal Natural, 2015)
N-hexane extracts of the bark from black plum(Syzygium cumini (L.) Skeels) showed activity againtSalmonella typhi. Meanwhile,  the result showed that N-hexane was not able to inhibit the  growth of Candida sp. The research was done at Microbiology laboratory, Biology Department Faculty of Mathemathics andScience,  Syiah Kuala University. The bark of black plum were collected from Aceh Besar District. The extraction method  for black plum used maceration with N-hexane and than concentrated in rotary evaporator. The disc diffusion method used to screen the antimicrobial activity with 20 %, 30 %, 40 % dan 50 % concentration.